Knowledge domain and trends in acupuncture for stroke research based on bibliometric analysis - Hao, Hongdong; Xing, Yifang; Chen, Jiashu; Wang, Haijun; Dong, Aiai; Liu, Hai-Xin (Frontiers in Human Neuroscience, 2025)
This bibliometric analysis comprehensively investigates the literature on acupuncture for stroke rehabilitation, aiming to identify key research hotspots, map the underlying knowledge structure, and examine developmental trends. The central hypothesis posits that acupuncture plays a pivotal role in enhancing neurological and motor function recovery in stroke patients, particularly when combined with complementary therapeutic modalities. A total of 2,217 relevant publications, spanning from database inception through 2024, were selected following stringent data screening and cleaning protocols. Utilizing advanced bibliometric tools such as CiteSpace and VOSviewer, we analyzed publication trends, leading authors, influential institutions, and citation networks. Our findings reveal a consistent and significant increase in research activity, with China emerging as the predominant contributor to this field. The analysis strongly emphasizes neurological recovery, motor function improvement, language rehabilitation, and the integration of acupuncture with other therapeutic strategies. Prominent keywords, including “acupuncture treatment,” “scalp acupuncture,” “electroacupuncture,” and “rehabilitation therapy,” reflect the evolving priorities within this domain. This study provides valuable evidence-based insights to guide future research on acupuncture for stroke rehabilitation, offering a solid framework for experimental investigations. By delineating the knowledge landscape, it contributes to refining research hypotheses and optimizing the clinical application of acupuncture in stroke recovery.Systematic review registrationhttps://inplasy.com/, INPLASY202530038.